Combination therapy of intravitreal ranibizumab and sub-tenon triamcinolone for treatment of resistant diabetic macular edema: a clinical study in Egypt - Hossam Eldin M. A. Khalil; Hazem E. Haroun; Alaa A. I. Shalan; Waleed M. Mahran (Beni-Suef University Journal of Basic and Applied Sciences)
Abstract Background Among those aged 20–74 in industrialized countries, diabetic retinopathy (DR) is the main cause of visual impairment. Diabetic macular edema (DME) is the leading cause of blindness in people with DR. DME that is resistant to therapy is now being treated with a number of different management strategies. This research was to examine the efficacy of sub-tenon steroid and anti- vascular endothelial growth factor (VEGF) injections as a combination therapy for the treatment of resistant DME, owing to the synergistic effect of this combination. Methods This is a two-arm, randomized, prospective clinical trial that included 100 eyes of patients with refractory DME divided into 2 equal groups: group 1 received posterior subtenon triamcinolone (STTA) and anti-VEGF injections (0.5 mg ranibizumab), and group 2 received anti-VEGF injections (0.5 mg ranibizumab) only, in the same session. The 2 groups were followed up for a period of 6 months. Results Group 1 showed significant improvements in best corrected visual acuity (BCVA) (from 0.20 ± 0.11 to 0.32 ± 0.12, p = 0.04) and central macular thickness (CMT) (from 393.2 ± 35.29 to 260.2 ± 11.43 µm, p = 0.001), with fewer injections required compared to Group 2. Recurrence rates were significantly higher in Group 2 (42% vs. 12%, p = 0.026). After injections, there was a noticeable rise in intraocular pressure (IOP) (16.02 ± 1.56 Vs 16.26 ± 1.24 in both groups respectively). However, this elevation is usually just transitory lasting for short periods of time and is within the safe, insignificant rise ranges. Conclusion The use of combined therapy with anti-VEGF treatment and STTA has been found to be an effective and safe approach to managing resistant DME. The lower number of injections needed help to reduce the economic burden, especially under constrained financial circumstances.